Pengaruh Komitmen Komunitas Merek Terhadap Loyalitas Merek: Nike Running Indonesia - , AGA CHRISTIE NUR V ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Brand loyalty has always been a priority for marketers. Variety of ways through a variety of means done with the aim of achieved consumer loyalty, one of which is through brand communities. Using brand community as a tool to achieve brand loyalty as the goal can not be granted, it takes the willingness of community members to committing to the brand communities. This study aims to analyze the influence of brand community commitment that established by the trust and affect on brand loyalty. This research samples were 138 respondents as the research object that is the members of Nike Running Indonesian as brand community. The data were analyzed using multiple regression analysis to examine the effect of trust and affect as a factor forming the brand community commitment and a simple regression analysis to examine the effect of brand community commitment to brand loyalty. From the research that has been conducted, the result shows that the community commitment variable are influenced positively by trust and affect on brand community shown to influence brand loyalty. In other words, trust and positive affect to brand community is able to increase the commitment of the brand community which increase brand loyalty.